2003
DOI: 10.1261/rna.5950603
|View full text |Cite
|
Sign up to set email alerts
|

Structural organization of a viral IRES depends on the integrity of the GNRA motif

Abstract: Little is known about the tertiary structure of internal ribosome entry site (IRES) elements. The central domain of foot-andmouth disease (FMDV) IRES, named 3 or I, contains a conserved GNRA motif, essential for IRES activity. We have combined functional analysis with RNA probing to define its structural organization. We have found that a UNCG motif does not functionally substitute the GNRA motif; moreover, binding of synthetic GNRA stem-loops to domain 3 was significantly reduced in RNAs bearing UCCG or GUAG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
117
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 90 publications
(126 citation statements)
references
References 50 publications
(44 reference statements)
9
117
0
Order By: Relevance
“…Interestingly, the GNRA motif and the C-rich loop are conserved in IRES elements classified as type I or II (Fernandez et al, 2011a;Yu et al, 2011b). The GNRA motif, which is essential for IRES activity in both FMDV and EMCV (Lopez de Quinto and Martinez-Salas, 1997; Robertson et al, 1999), adopts a tetraloop conformation (Fernandez-Miragall and Martinez-Salas, 2003;Phelan et al, 2004), and determines long-range interactions (Fernandez-Miragall et al, 2006;Ramos and Martinez-Salas, 1999). Domain 4 consists of a Yshape RNA structure (corresponding to subdomains J and K) and provides the binding-site for eIF4G (Bassili et al, 2004;Kolupaeva et al, 1998;Lopez de Quinto and Martinez-Salas, 2000;Lozano et al, 2014).…”
Section: Picornavirus Ires Elements Diversitymentioning
confidence: 99%
“…Interestingly, the GNRA motif and the C-rich loop are conserved in IRES elements classified as type I or II (Fernandez et al, 2011a;Yu et al, 2011b). The GNRA motif, which is essential for IRES activity in both FMDV and EMCV (Lopez de Quinto and Martinez-Salas, 1997; Robertson et al, 1999), adopts a tetraloop conformation (Fernandez-Miragall and Martinez-Salas, 2003;Phelan et al, 2004), and determines long-range interactions (Fernandez-Miragall et al, 2006;Ramos and Martinez-Salas, 1999). Domain 4 consists of a Yshape RNA structure (corresponding to subdomains J and K) and provides the binding-site for eIF4G (Bassili et al, 2004;Kolupaeva et al, 1998;Lopez de Quinto and Martinez-Salas, 2000;Lozano et al, 2014).…”
Section: Picornavirus Ires Elements Diversitymentioning
confidence: 99%
“…The first 85 nt on the 59 end encompasses domain 2 (also termed H); it consists of a stem-loop that contains a binding site for the polypyrimidine tract-binding protein (PTB) (Luz and Beck 1991). Second, the central domain (termed 3 or I, encompassing nucleotides 86-299) is a selffolding region that adopts a cruciform RNA structure (Fernandez-Miragall and Martinez-Salas 2003) including internal RNA-RNA interactions (Fernandez-Miragall et al 2006). Third, on the 39 end of the IRES, domains 4 and 5 (or J-K and L, encompassing nucleotides 300-462) determine RNA-protein interactions involving translation initiation factors, eIF4G, eIF4B, eIF3, and auxiliary proteins as PTB (Lopez de Quinto and Martinez-Salas 2000; Pilipenko et al 2000;Lopez de Quinto et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis is in agreement with earlier proposals in which nucleotides belonging to the GNRA motif, the RAAA stem-loop and G 240 within the C-rich bulge are linked in the three-dimensional RNA structure. 12,57 As demonstrated by mutational and RNA probing studies, domain 3 plays a fundamental role in dictating the formation of a constrained structure likely providing the correct orientation to recruit the ribosome subunits to the initiation site. 10 Therefore, the conformational changes induced by IRAB would result in a misfolded IRES structure leading to diminished internal translation initiation, as observed in the translation assays reported here.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6] Functional and structural analysis have shown that the FMDV IRES is organized in 5 structural domains of which domain 2 includes a polypyrimidine tract that provides the polypyrimidine tract-binding protein (PTB) binding site. 11 Domain 3 consists of 210 nucleotides, the most apical region of which is arranged as a cruciform structure 12 that harbors conserved motifs. Disruption of these motifs abrogates IRES activity, in addition to altering distant RNA-RNA interactions.…”
Section: Introductionmentioning
confidence: 99%